Pathways to Abortion at a Tertiary Care Hospital: Examining Obesity and Delays. Issue 1 (15th January 2019) - Frarey, Alhambra; Schreiber, Courtney; McAllister, Arden; Shaber, Allison; Sonalkar, Sarita; Sammel, Mary D.; Long, Judith A.
Abstract : CONTEXT: Advancing gestational age can increase the cost of an abortion and is a significant risk factor for complications. While obesity is not associated with increased risks, anecdotal evidence suggests that obese women seeking services at freestanding abortion clinics are often referred for hospital‐based care, which can lead to delays . METHODS: In 2016, a cross‐sectional survey collected data on the experiences of 201 women who had obtained abortions at a hospital‐based clinic in Philadelphia; rates of medical complications were determined from hospital records. Multivariable logistic regression analysis was used to assess if obesity was associated with whether patients had been referred from freestanding abortion clinics or reported other paths to care. Differences in wait time and up‐front out‐of‐pocket costs were examined by women's referral status . RESULTS: No difference in rates of abortion complications was found between patient groups. Women who were severely obese (body mass index of at least 40 kg/m 2 ) were more likely than normal‐weight individuals to have been referred from a freestanding abortion clinic (odds ratio, 7.5). The median wait time to get an abortion was 28 days for referred patients and 12 days for others. Multivariable analysis confirmed that referred patients waited twice as long as other patients (rate ratio, 2.0) and paid 66% more in up‐front costs . CONCLUSIONS: Future research is needed to determine whether obese women seeking abortions are being referred despite evidence that they do not require hospital‐based care. If obese women are suffering delays because of referral, strategies to help overcome delay should also be explored .